PENERAPAN METODE MULTI ATTRIBUTE UTILITY THEORY UNTUK KLASIFIKASI PENENTUAN KELAS SANTRI BARU PONDOK PESANTREN AN NAJAH DENANYAR JOMBANG - Misbakhuddin Misbakhuddin; Hadi Sucipto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research creates an online support system for decision-making that utilizes the Multi Attribute Utility Theory (MAUT) technique to sort incoming students at Pondok Pesantren An Najah Denanyar Jombang into standard and advanced classes. The previous method of assigning students was susceptible to errors. Designed with PHP and MySQL following a waterfall approach, the system assesses students on four factors: Pegon literacy along with fundamental knowledge of tauhid, fiqh, and tajwid. MAUT is employed to calculate preference scores, which are then evaluated against a central value for class allocation. Black box testing verified that all 20 samples of data were consistent with earlier manual assessments, achieving a precision rate of 99%. This system enhances the fairness and effectiveness of decisions regarding class placements.